fi001045: Climaxi. Actie voor een sociaal klimaat - De Bodt, Filip; Kane, Tourad; Boukhzar, Aziz; Hutse, Sarah; Deblauwe, Koenraad; 't Uilekot; Victoria Deluxe
"Documentaire, film over de klimaatverandering."